FANGIRLS AND FAKE NEWS: DIGITAL ETHNOGRAPHY AND THE AFFECTS OF FANDOM - McCann, Hannah; Southerton, Clare (AoIR Selected Papers of Internet Research, 2019)
This paper draws on a digital ethnography conducted via Twitter, of a controversial subnetwork of fans of boyband One Direction known as “Larries”. The Larry fandom is built around imagining a romantic relationship exists between One Direction band members Harry Styles and Louis Tomlinson, referred to by the portmanteau “Larry”. Imagining relationships between celebrities is a controversial practice known in fan communities as “Real Person Slash” (RPS). For this practice Larries have been framed within popular media as conspiracy theorists. Our study sought to examine whether a more complex and nuanced understanding of the fandom was possible, particularly regarding relationships and community building in this fandom. Through digital ethnographic methods, we explored how the practices of Larries create a space in which new and unexpected desires, identities, intimacies and relations are constituted. Between March and July 2018, we followed approximately 490 public accounts, kept a fieldnote diary, and conducted semi-structured interviews with seven active users via direct messenger. Conducting observations on a daily basis over an extended period as regular fans would, we became privy to the highs, lows, excitement, and tensions of the group, that may be otherwise obscured. This study raises questions about what might be missed in studying controversial groups at a macro level only. This paper considers the benefits of undertaking qualitative digital ethnographic work and discuss the affective flows of digital networks on social media that might remain obscured by other digital methods.